2005
DOI: 10.1021/ja056150x
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective TADMAP-Catalyzed Carboxyl Migration Reactions for the Synthesis of Stereogenic Quaternary Carbon

Abstract: The chiral, nucleophilic catalyst TADMAP (1) has been prepared from 3-lithio-4-dimethylaminopyridine (5) and triphenylacetaldehyde (3), followed by acylation and resolution. TADMAP catalyzes the carboxyl migration of oxazolyl, furanyl, and benzofuranyl enol carbonates with good to excellent levels of enantioselection. The oxazole reactions are especially efficient, and are used to prepare chiral lactams (23) and lactones (30) containing a quaternary asymmetric carbon. TADMAP-catalyzed carboxyl migrations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(84 citation statements)
references
References 87 publications
(53 reference statements)
1
80
0
3
Order By: Relevance
“…[70] Recent reports have further expanded this method to furanones, benzofuranones, and oxindoles, thus making it a general method for the generation of quaternary carbon stereocenters. [71] In related work, it was shown that silyl ketene acetals and silyl ketene imines are also capable of intercepting N-acylpyridinium ion intermediates, further highlighting the utility of Lewis base catalysis for the generation of quaternary carbon stereocenters. [72] Novel extensions of this general reaction class are found with variations of the nucleophile structure (Scheme 12).…”
Section: Extending the Electrophilic Reactivity Of Acylated Lewismentioning
confidence: 99%
“…[70] Recent reports have further expanded this method to furanones, benzofuranones, and oxindoles, thus making it a general method for the generation of quaternary carbon stereocenters. [71] In related work, it was shown that silyl ketene acetals and silyl ketene imines are also capable of intercepting N-acylpyridinium ion intermediates, further highlighting the utility of Lewis base catalysis for the generation of quaternary carbon stereocenters. [72] Novel extensions of this general reaction class are found with variations of the nucleophile structure (Scheme 12).…”
Section: Extending the Electrophilic Reactivity Of Acylated Lewismentioning
confidence: 99%
“…[70] In neueren Arbeiten wurde das Verfahren auf Furanone, Benzofuranone und Oxindole angewendet und als allgemeine Methode zum Aufbau quartärer Kohlenstoffchiralitätszentren etabliert. [71] In einer ähnlichen Arbeit wurde beschrieben, dass N-Acylpyridiniumionen auch durch Silylketenacetale und Silylketenimine abgefangen werden können; dabei werden ebenfalls durch Lewis-Base-Katalyse quartäre Kohlenstoffchiralitätszentren gebildet. [72] Neuartige Anwendungen dieser allgemeinen Reaktion betreffen Nucleophile mit anderen Strukturen (Schema 12).…”
Section: Umfang Des Aufsatzesunclassified
“…When the reaction was conducted in the absence of NMM, 4a was formed in a low yield (4%) with the recovery of 3a (96%), and 5a was not formed at all, indicating that a base is essential for the completion of cyclodehydration. [12][13][14][15] On the basis of the assumption that the yield of oxazole derivative 5a could be decreased by the separation of relatively lipophilic 4a from water-soluble DMT-MM, we conducted the reaction in a biphasic solvent system composed of CH 2 Cl 2 -acetone-H 2 O (1 : 1 : 1). As a result, the yield of 5a decreased Regular Article…”
Section: Resultsmentioning
confidence: 99%